The Influence of Neurocognitive Impairment on HIV Risk Behaviors and Intervention Outcomes among High-Risk Substance Users: A Systematic Review - Shrestha, Roman; Copenhaver, Michael (Frontiers in Public Health, 2016)
Neurocognitive impairment (NCI) among high-risk substance users poses a substantial barrier to reducing risk behaviors in this populations. Previous work suggest that NCI is intertwined in a close, reciprocal relationship with risk behaviors. Not only does substance use worsen cognitive impairment, but cognitive impairment may also reduce the efficacy of interventions aimed at reducing risk and improving medication adherence. In this systematic review, we examine the potential impact of substance abuse and cognitive functioning in the context of HIV risk behaviors and risk-reduction intervention outcomes. The findings thus far suggest that, in order to be effective, risk-reduction interventions must take into account the impact of NCI on learning, memory, and behavior.